Shia revival and Welayat Al-Faqih in the Making of Iranian foreign policy - Salamey, Imad (2011)
The repercussions of the 1979 Iranian Revolution are too often attributed to the idea that the state's policy-making was based on a Khomeinist-charged ideology that sought to expand political Islam throughout the Middle East. Alternative interpretations of Iranian foreign policy have emphasized policymakers' pragmatic, as opposed to ideological, considerations of state preservation. This article examines these contested propositions regarding the motivations shaping Iranian foreign policy. It assesses three interrelated foreign policy drivers that have been particularly salient in framing the Iranian positions vis-à-vis the various changes in both the regional and international arenas: Shiism, Welayat Al-Faqih, and domestic policy struggles. Analysis of Iranian foreign policy reveals that it is constructed on Iran's various regional rapprochements that take into strong consideration domestic politics. The findings suggest that Iran's foreign policy – be it the country's nuclear program, its animosity towards Israel and the US, or its support of diverse proxy groups in the Middle East – cannot be rationalized solely on assumptions of the state's self-preservation. Alternatively, this paper concludes that Iranian foreign policy is strongly shaped by Shia revival and Welayat Al-Faqih ideological discourses.